Truth Dare Card Media Develoment Improving the Abilty to think Creatively Pancasila Value Material Class V SDN Modangan 05 Blitar - Ula Adiniyatul Mukaromah; Cindya Alfi; Mohamad Fatih (Edumaspul: Jurnal Pendidikan, 2024)
The aim of this research is to develop truth or dare card media to improve creative thinking skills regarding Pancasila value material for class V at Modangan 05 Blitar Elementary School. This research utilizes research and development (R&D) techniques where the approach uses ADDIE, which stands for Analysis, Design, Development, Implementation, and Evaluation. Primary data collected from the field is the backbone of this research data collection. This data source comes from experts, instructors and students. The researchers used interviews and questionnaires as data collection strategies in this research. Carry out product testing in the field using methods such as observation, consulting with material experts, seeking input from media experts, and providing questionnaires to students as well as N-gain tests. According to the findings of material experts, the validity of the criteria was assessed as "very valid" with a score of 88%. The media expert's evaluation received a score of 100% and was rated "Very Valid" according to the criteria. The media feasibility study gave a result of 88.5%. The test results showed a significant value, indicating that the Truth or Dare card medium was accepted. In addition, there was an increase observed between the pre-questionnaire and post-questionnaire, which shows that the application of the Truth and Dare game media effectively improves students' creative thinking skills at SDN Modangan 05.